2010
DOI: 10.1016/j.jaci.2009.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Infected atopic dermatitis lesions contain pharmacologic amounts of lipoteichoic acid

Abstract: Background-Bacterial infection with Staphylococcus aureus is a known trigger for worsening of atopic dermatitis (AD); the exact mechanisms by which bacterial infection worsens dermatitis are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 34 publications
1
87
0
Order By: Relevance
“…Subsequently, S. aureus promotes AD by stimulating a strong proinflammatory response (7). S. aureus proteins, such as hemolysin ␣ (HLA), staphylococcal protein A (SPA), and lipoteichoic acids (LTA), promote proinflammatory cytokine production from keratinocytes (7)(8)(9)(10)(11). However, this stimulation requires the concurrent presence of a surfactant, such as SDS (11).…”
mentioning
confidence: 99%
“…Subsequently, S. aureus promotes AD by stimulating a strong proinflammatory response (7). S. aureus proteins, such as hemolysin ␣ (HLA), staphylococcal protein A (SPA), and lipoteichoic acids (LTA), promote proinflammatory cytokine production from keratinocytes (7)(8)(9)(10)(11). However, this stimulation requires the concurrent presence of a surfactant, such as SDS (11).…”
mentioning
confidence: 99%
“…6 Lipoteichoic acid (LTA), another cell wall component of S. aureus, is widely present in AD skin lesions, and its amount detected in the skin correlate with the severity of AD. 7 Although it has long been postulated that superficial infection with S. aureus contributes to AD pathophysiology, the underlying detailed relationship between S. aureus infection and allergic inflammation in AD remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study suggested that lipoteichoic acid (LTA), a cell wall component of S. aureus, might amplify skin inflammation in AD [4]. Furthermore, Travers et al have demonstrated the presence of high levels of staphylococcal LTA in AD lesions [5]. However, the relationship between LTA and IL-5 production in patients with AD has not been fully elucidated.…”
mentioning
confidence: 99%
“…Therefore it is likely that Th2 cells in PBMCs from AD patients may have already been primed by intracellular signaling through the T-cell receptor-CD3 surface complex. Since LTA is known to be a ligand for toll-like receptor (TLR) 2 [5], LTA would probably stimulate the TLR2 of antigen-presenting cells (APCs) among PBMCs. This would enhance the expression of CD80/CD86 on APCs and deliver a second signal to the primed Th2 cells through interaction between CD80/CD86 on APCs and CD28 on Th2 cells, resulting in augmentation of IL-5 production.…”
mentioning
confidence: 99%